Omer Parent : artiste-décorateur - de Andrade, Marie-Maxime (RACAR : Revue d'art canadienne / Canadian Art Review, 2021)
Since their emergence in the nineteenth century, department stores have capitalized on the work of various artists and creators in order to fashion their visual identity. Yet, this close relationship between these stores’ commercial enterprise and the arts is rarely acknowledged. This article explores, through a case study, the visual spectacle offered by Henry Morgan & Co., one of Montreal’s main department store during the 1920s and 1930s. Omer Parent (1907–2000), founding director of the Laval University School of visual arts, worked at this store from 1929 to 1936 as chief “artist decorator.” His involvement in the construction of Morgan’s visuality not only allowed him to make a living out of his art but also to play an active role during this period in the dissemination of new trends and fashion in Montreal. This article highlights Omer Parent’s contribution to the promotion of modern aesthetics in Quebec during the 1920s and 1930s as well as demonstrating the advent of interior design expertise in the province.